Effects of permafrost thaw on nitrogen availability and plant–soil interactions in a boreal Alaskan lowland. (6th September 2016) - Finger, Rebecca A.; Turetsky, Merritt R.; Kielland, Knut; Ruess, Roger W.; Mack, Michelle C.; Euskirchen, Eugénie S.
Summary: Increasing rates of permafrost thaw in boreal peatlands are converting conifer forests to waterlogged open wetlands. Permafrost thaw increases soil nitrogen (N) availability, but it is unclear whether such changes are due solely to changes in surface soil N mineralization or N mobilization from thawing permafrost soils at depth. We examined plant species composition and N availability along triplicate permafrost thaw gradients in Alaskan peatlands. Each gradient comprised four community types including: (i) a permafrost peatland with intact permafrost, (ii) a drunken forest experiencing active thaw, (iii) a moat representing initial complete thaw and (iv) a collapse scar bog representing several decades of post‐thaw succession. Concentrations of dissolved organic (DON) and inorganic N (DIN) in the upper 60 cm of soil increased along the permafrost thaw gradients. The drunken forest had the greatest mean concentrations of total dissolved N relative to the other community types, primarily due to greater concentrations of large molecular DON. The moat and collapse bog had significantly greater inorganic N concentrations than the permafrost or drunken forest, suggesting that changes in N availability are not a short‐term effect, but can be sustained for decades or centuries. Across all plant community types, DIN and DON concentrations increased with soil depth during maximum seasonal ice thaw (September), suggesting that deeper soil horizons are important reservoirs of N post‐thaw. Vegetation responses to permafrost thaw included changes in plant community composition shifting from upland forest species to hydrophilic vegetation with deeper rooting profiles in the collapse scar bogs and changes in foliar N and δ 15 N values. N concentrations in plant foliage and litterfall increased with concentrations of DIN during collapse bog succession, suggesting that plants are utilizing additional mineralized N. Synthesis . Our results suggest that the conversion of forest to wetlands associated with permafrost thaw in boreal lowlands increases N availability, at least in part by increasing turnover of deep soil organic matter. Plants appear to utilize these additional deeper N sources over timescales of years to centuries following permafrost thaw. Abstract : Climate change is creating widespread permafrost thaw and changing boreal forest carbon cycling dynamics, yet few studies have examined post‐thaw changes to nitrogen cycling. This study demonstrates that as lowland forests convert to wetlands following permafrost thaw, N availability increases. Plants appear to utilize additional deeper N sources over timescales of years to centuries following permafrost thaw.